2019
DOI: 10.1002/tkm2.1230
|View full text |Cite
|
Sign up to set email alerts
|

Development of a medical education program with abdominal palpation simulators to support the understanding of traditional Japanese (kampo) medicine in beginners

Abstract: Aim Traditional Japanese (kampo) medicine has recently been included in the medical education curriculum in Japan; hence, an education program in kampo physical examination for beginners is needed. The aim of the present study was to develop an education program using a simulator of kampo abdominal palpation that would enable beginners to acquire this skill, and to assess the effectiveness and usefulness of the education program. Methods First, we conducted a preliminary trial. Fifteen beginners received a lec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…More recently, we conducted a practical session on abdominal diagnosis using the current version of the Fukushin simulator with medical students, and 98.4% of the students gave positive feedback (Yakubo et al, 2014b). Arita et al developed an education program including a general lecture on physical examination in Kampo medicine, followed by a pre-test assessment involving palpation of the simulators, a specific lecture about abdominal palpation, and finally a post-test assessment (Arita et al, 2019). Their education program using simulators for Kampo abdominal palpation can be effective and useful for beginners in Kampo medicine.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we conducted a practical session on abdominal diagnosis using the current version of the Fukushin simulator with medical students, and 98.4% of the students gave positive feedback (Yakubo et al, 2014b). Arita et al developed an education program including a general lecture on physical examination in Kampo medicine, followed by a pre-test assessment involving palpation of the simulators, a specific lecture about abdominal palpation, and finally a post-test assessment (Arita et al, 2019). Their education program using simulators for Kampo abdominal palpation can be effective and useful for beginners in Kampo medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The best educational effect observed in our study appeared after we added abdominal examination simulator training. A previous study reported that the introduction of an abdominal examination simulator improved the educational effect among beginners learning Kampo medicine [1]. Using the abdominal examination simulator allowed the learners to experience a practical examination method, and thus, could easily imagine the clinical situation in traditional Kampo clinical reasoning, which started the learning cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly the abdominal examination was difficult to learn because it is sensory and subjective. To learn this method of abdominal examination, an abdominal examination simulator was developed and has been used in education [1].…”
Section: Introductionmentioning
confidence: 99%